2021
DOI: 10.3390/genes12050650
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between Expression of FOXC2 and Its lncRNA in Lymphedema-Distichiasis Caused by Frameshift Mutations

Abstract: Forkhead-box C2 (FOXC2) is a transcription factor involved in lymphatic system development. FOXC2 mutations cause Lymphedema-distichiasis syndrome (LD). Recently, a natural antisense was identified, called lncRNA FOXC2-AS1, which increases FOXC2 mRNA stability. No studies have evaluated FOXC2 and FOXC2-AS1 blood expression in LD and healthy subjects. Here, we show that FOXC2 and FOXC-AS1 expression levels were similar in both controls and patients, and a significantly higher amount of both RNAs was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In a non-cancer context, the same mechanism might regulate lymphatic valve formation and collecting lymphatic vessel specialization. Based on Zhang et al [ 208 ] and Missaglia et al [ 216 ]. eIF4F eukaryotic initiation factor 4F, m7G methyl-7-guanosine (cap), miRISC microRNA-induced silencing complex, ORF open reading frame, PABP poly(A)-binding protein …”
Section: Anril and Gas5mentioning
confidence: 99%
See 1 more Smart Citation
“…In a non-cancer context, the same mechanism might regulate lymphatic valve formation and collecting lymphatic vessel specialization. Based on Zhang et al [ 208 ] and Missaglia et al [ 216 ]. eIF4F eukaryotic initiation factor 4F, m7G methyl-7-guanosine (cap), miRISC microRNA-induced silencing complex, ORF open reading frame, PABP poly(A)-binding protein …”
Section: Anril and Gas5mentioning
confidence: 99%
“…Recently experimental evidence has emerged suggesting that at least some of the above FOXC2-AS1 -mediated mechanisms are operational in non-cancer cells. Missaglia et al [ 216 ] detected endogenous expression of FOXC2-AS1 in blood cells of healthy individuals and LD patients. Furthermore, they found that, consistent with the results obtained in cancer cell lines, endogenous FOXC2-AS1 positively regulates the expression of wild-type FOXC2 and its frameshift LD mutant in normal, non-cancer cells.…”
Section: Lncrna-mediated Control Of the Master Regulator Of Lymphatic...mentioning
confidence: 99%
“…The expression of PROX1 is regulated by SOX18 and GATA2, while the latter also controls the expression of FOXC2 [12]. FOXC2, a member of the forkheadbox (FOX) family, regulates the development of several systems during embryogenesis, particularly the lymphatic and blood vascular system [75,76].…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Among them, NR2F2 is negatively regulated by NOTCH signaling through HEY2 expression [77]. Moreover, they can activate FOXC2, such as CDK5 and FOXC2-AS1 [75,78]. PROX1 and FOXC2 expression is also increased by CHD5 through the β-catenin pathway, regulating lymphatic vessels and valve development [79,80].…”
Section: Transcription Factorsmentioning
confidence: 99%